Clinicoradiological Profile of Lower Lung Field Tuberculosis Cases among Young Adult and Elderly People in a Teaching Hospital of Madhya Pradesh, India - Saurabh Kumar Singh; Kamlesh Kumar Tiwari (Journal of Tropical Medicine)
Aim. To study the clinical and radiological features of lower lung field tuberculosis (LLFTB) in relation to the patients of nonlower lung field tuberculosis (non-LLFTB). Material and Methods. All the patients of lower lung field tuberculosis defined by the lesions below an arbitrary line across the hila in their chest X-rays were included in the study. Their sputum for acid fast bacilli, HIV, blood sugar, and other relevant investigations were performed. Results. The total of 2136 cases of pulmonary tuberculosis was studied. Among them 215 (10%) cases of patients were diagnosed as the case of lower lung field tuberculosis. Females (62%) were more commonly affected. Most common clinical feature in non-LLFTB was cough (69%) followed by fever (65%), chest pain (54.7%), and weight loss (54.4%). Chest X-ray showed predominance of right side (60.9%) in cases of LLFTB. The relative risk of having the LLFTB in diabetes patients, HIV seropositive patients, end stage renal disease patients, and patients on corticosteroid therapy was high. Conclusion. Lower lung field tuberculosis is not an uncommon entity. It is more common in diabetes, HIV positive, end stage renal disease, and corticosteroid treated patients. Clinical and radiological features are different from upper lobe tuberculosis patients.